2006
DOI: 10.3748/wjg.v12.i36.5853
|View full text |Cite
|
Sign up to set email alerts
|

Doppler study of hepatic vein in cirrhotic patients: Correlation with liver dysfunction and hepatic hemodynamics

Abstract: Doppler waveforms of hepatic vein, which is independent of liver dysfunction, should be obtained during normal respiration. Mean hepatic vein velocity reflects the change in hepatic circulation associated with progression of liver cirrhosis. It can be used as a new parameter in the assessment of liver cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 17 publications
0
15
1
Order By: Relevance
“…Some studies have reported that liver function tends to worsen in cases with a flat pattern (Bolondi et al 1991;Kawanaka et al 2008), whereas another study found no significant relationship between HV waveform pattern and liver function (Sudhamshu et al 2006), probably attributable to a different patient population. Our study found that there were no significant relationships between Child-Pugh or MELD scores and HV waveform pattern.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Some studies have reported that liver function tends to worsen in cases with a flat pattern (Bolondi et al 1991;Kawanaka et al 2008), whereas another study found no significant relationship between HV waveform pattern and liver function (Sudhamshu et al 2006), probably attributable to a different patient population. Our study found that there were no significant relationships between Child-Pugh or MELD scores and HV waveform pattern.…”
Section: Discussionmentioning
confidence: 96%
“…The triphasic waveform pattern is common in normal patients and patients without cirrhosis: 100% in controls (50/50 [Colli et al 1994] and 65/65 [Bolondi et al 1991]) and 100% in controls and patients with chronic hepatitis (30/30) (Sudhamshu et al 2006). Meanwhile, various waveform patterns have been detected in patients with cirrhosis: triphasic in 50%, biphasic in 31.7% and flat in 18.3% of those with cirrhosis (Bolondi et al 1991); triphasic in 49% (49/100), biphasic in 48% (48/100) and flat in 3% (3/100) of patients with cirrhosis (Sudhamshu et al 2006); and triphasic in 31%, biphasic in 35% and flat in 12% of patients with portal hypertension (Ohta et al 1994). One of the novel points of our study was the use of quantitative measurement to classify the HV waveform pattern.…”
Section: Discussionmentioning
confidence: 99%
“…With both methods agreement is worst at a flow rate of 1.0 ml/s [13]. Assessing venous blood flow is also important, as in the assessment of hepatic cirrhosis [14], venous injuries or deep vein thrombosis [15]. There is a well known deviation between the true and the flow as visually estimated from angiography.…”
Section: Discussionmentioning
confidence: 99%
“…This approach omits the need for repeated scans. With flow rates of up to approximately 14 cm/s, the reported technique has the potential to assess portal and hepatic venous flow as well as common femoral venous flow, which are in the range of 12-20 cm/s [14,15,19]. This technique allows calculation of blood flow from the same data set that is used for imaging of three-dimensional anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…As it will be shown in a sensitivity analysis, this parameter does not influence the distribution of organ blood flow); Cardiac output increases by 13.3% at each stage of cirrhosis [corresponds to 45% increase in Child Pugh C, see Fig. A and references ]; Both the gastrointestinal bed ( R GI ) and hepatic artery ( R exHA ) are vasodilated ; values for R GI , R exHA and %Shunt w ere selected, such that the resulting distribution of organ blood flow satisfied the following two conditions: Mean arterial pressure ( MAP ) decreases with grade of liver disease ; Hepatic perfusion is maintained or decreases at each stage . …”
Section: Methodsmentioning
confidence: 99%